O empatii w nauce według Anny Kingsford .......... 89 - Banaszkiewicz, Magdalena; Golemo, Karolina; Duda, Anna; Czech, Franciszek; Banaś, Monika (Peregrynacje międzykulturowe: Księga jubileuszowa dedykowana prof. Tadeuszowi Palecznemu, 2025)
ABOUT EMPATHY IN SCIENCE ACCORDING TO ANNA KINGSFORDThe text is dedicated to Anna Kingsford, a feminist, activist, and physician who lived in the second half of the 19th century. Her attitude, worldview, actions, and professional and social work were driven by the conviction of the necessity of incorporating empathy into scientific research. Observing the context of late Victorian England and France, she strongly criticized the then-common belief in the utilitarian treatment of living beings, who lacked the strength to defend themselves. She drew her arguments by combining currents of scientific materialism with Neoplatonism, Theosophy, Hermeticism, Spiritualism, and Esotericism. The result was an extraordinary sensitivity that allowed her to carry out her medical mission while fully adhering to the principle of primo non nocere.